Persian Translation and Psychometric Properties of Professional Quality of Life Scale (ProQOL) for Health Care Providers - Maryam Ghorji; Zohreh Keshavarz; Abbas Ebadi; Malihe Nasiri (Journal of Mazandaran University of Medical Sciences, 2018)
BBackground and purpose: Professional quality of life is a concept felt by an individual in relation to their jobs. Positive and negative aspects of a job influence professional quality of life. Evaluation of professional quality of life requires reliable scales. The current study aimed at translating (into Persian) and examining the psychometric properties of professional quality of life scale for health care service providers. Materials and methods: This methodological research was conducted in 464 physicians, midwives and nurses working in hospitals of Qazvin province, using convenience sampling. Based on permission from the developer of the scale, it was back translated. Face validity, content validity, and exploratory and confirmatory factor analyses were tested. Test-retest and internal consistency were used to evaluate the reliability of the questionnaire. Results: Confirmatory factor analysis showed that items 1, 4, 15, 17, and 29 did not present significant factor loadings (<0.3), therefore, they were discarded. Factor loadings for other items varied from 0.32 to 0.69. Goodness of fit measures was as follows: Normed Fit Index (NFI(: 0.93; Non Normed Fit Index )NNFI(: 0.95; Goodness of Fit Index )GFI(: 0.84; Comparative Fit Index (CFI:(0.95; X2/ Degrees of freedom )X2/df(:2.9, and Root Mean Square Error (RMSE(: 0.07 (P<0.001). Intra-class reliability of the scale was 0.96. Also, reliability of the scale was 0.73 based on internal consistency (Cronbach's alpha). Conclusion: Present study showed that the modified Persian version of Professional Quality of Life Scale (ProQOL) consisting of 25 items could be used as a valid and reliable instrument in assessing professional quality of life in physicians, midwives, and nurses.